Comparison of the of BBAP and CDDP in Fragaria sp. Polymorphism Analysis - Silvia Farkasová; Lucia Urbanová; Jana Žiarovská; Matúš Kyseľ; Alžbeta Jauschová; Lenka Kučerová; Miroslava Kačániová (Scientific Papers Animal Science and Biotechnologies)
Strawberries are popular worldwide for their nutritional benefits. Their germplasm is widely analysed by different molecular and DNA based markers. Here, two different marker techniques were used to analyze intra- and interspecies variability of 38 genotypes of two strawberry species (Fragaria x ananassa and Fragaria vesca L.). Bet v 1 based amplified polymorphism (BBAP) and conserved DNA-derived polymorphism (CDDP) utilized to obtain specific fingerprints. BBAP technique generated lower polymorphism comparing to CDDP (BBAP – 99.01%, CDDP – 99.65%), but both of the techniques separated all of the analysed strawberry genotypes. The groups of genotypes in constructed dendrograms were not clustered according the specie specificity.